Lebanese Experiences and the Challenges of Everyday Live in Poland - Rafał Wiśniewski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article addresses the issue of pluralism in the axiological and normative area which affects Polish-Lebanese relations. It presents the findings of a research on the Lebanese community in Poland. The research gives insight into Lebanese citizens' motivations for moving to Poland and their opinions on everyday life in this country.